Rate Pressure Products Affect the Relationship between the Fractional Flow Reserve and Instantaneous Wave-Free Ratio - Suguru Ebihara; Hisao Otsuki; Hiroyuki Arashi; Junichi Yamaguchi; Nobuhisa Hagiwara (Journal of Interventional Cardiology)
The rate pressure product (RPP) is an index of myocardial metabolism that correlates closely with myocardial hemodynamics. The relationship between the RPP and the fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) is not known. In this study, we investigated the effects of the RPP on the FFR and iFR. We retrospectively enrolled 195 patients (259 lesions) who had undergone invasive coronary angiography and both the iFR and FFR examinations between 2012 and 2017. The RPP was defined as systolic blood pressure multiplied by the heart rate, measured prior to the iFR evaluation. The study population was divided into the low-RPP (n = 129, mean RPP: 6981 ± 1149) and high-RPP (n = 130, mean RPP: 10391 ± 1603) groups according to the median RPP. Correlations and biases between the iFR and FFR were compared. The diagnostic performance of the iFR in the groups was calculated, using FFR as the gold standard. The correlation between the iFR and FFR was higher in the high-RPP group than in the low-RPP group. The bias between the iFR and FFR in the high-RPP group was smaller than that in the low-RPP group. The best cutoff value of the iFR for predicting an FFR of 0.8 was 0.90 for all lesions, 0.93 for the low-RPP group, and 0.82 for the high-RPP group. The iFR and RPP showed a weak but a statistically significant negative correlation (R = 0.14; p=0.029). This was not observed for the relationship between the FFR and RPP. In conclusion, the RPP affects the relationship between the FFR and iFR. With FFR as the gold standard, the iFR may underestimate and overestimate the functionality of ischemia in the low- and high-RPP groups, respectively.